2019
DOI: 10.21608/adjg.2019.7780.1100
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Cortactin, E-Cadherin, and MDM2 Proteins in Solid Ameloblastoma versus Odontogenic Keratocyst (An immunohistochemical study)

Abstract: Purpose:The extent of invasion can be analyzed by the expression and production of various genes and proteins by lesional cells. However, current clinical parameters lack the potential to predict the neoplastic behavior in solid ameloblastoma (SAB) and odontogenic keratocyst (OKC). Cortactin, an F-actin binding protein, overexpression has been correlated with advanced clinic pathological stage and poor prognosis in several tumors. E-cadherin belongs to the classical cadherins which. Low E-cadherin expression c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…More than 75% of stellate reticulum cells showed mainly membranous expression while 75% of the peripheral columnar cells showed negative expression. These findings were similar to those of Abd Elsamia et al, who reported that distribution of immune reaction for Ecadherin was noted on the cell membrane mainly in the central stellate reticulum-like cells than peripheral columnar cells of CMAM [17] . These findings were also in agreement with previous studies which demonstrated that the pattern of E-cadherin immunoreactivity was predominantly on the membrane at cell-cell borders and the most intense reactivity was noticed in the stellate-reticulum like cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More than 75% of stellate reticulum cells showed mainly membranous expression while 75% of the peripheral columnar cells showed negative expression. These findings were similar to those of Abd Elsamia et al, who reported that distribution of immune reaction for Ecadherin was noted on the cell membrane mainly in the central stellate reticulum-like cells than peripheral columnar cells of CMAM [17] . These findings were also in agreement with previous studies which demonstrated that the pattern of E-cadherin immunoreactivity was predominantly on the membrane at cell-cell borders and the most intense reactivity was noticed in the stellate-reticulum like cells.…”
Section: Discussionsupporting
confidence: 91%
“…Since the prognosis of various neoplasms including odontogenic tumors cannot be reliably and accurately predicted on the basis of clinical and histopathologic features only, it is highly desirable to find genetic markers to rely on. These genetic markers could be an objective measure to clarify alterations that might be occurring during the process of tumorigenesis [17] . Taking this into consideration, this study was designed to assess the immunohistochemical expression of E-cadherin and OPN in CMAM and HAM, correlate their expression to each other and to predict their prognostic value in these tumors.…”
Section: Discussionmentioning
confidence: 99%